Aspectos históricos, teórico-metodológicos e pedagógicos do Teatro do Oprimido na perspectiva de Augusto Boal - Portes, Carolina Marcon (2019)
In this dissertation we aimed to analyze the historical, theoretical-methodological and pedagogical aspects of Augusto Boal's Theater of the Oppressed (1931-2009), singularly regarding his unity theoretical-methodological on the perspective of human formation, exhibited above all, on the following works The Theater of the Oppressed and other Political Poetics (2013) and Games for Actors and Non-Actors (2008), both literary works of the theatrologist. On this bibliographical research, we prioritize the works of Boal, the primary source of the research. As secondary sources, from survey made in the physical and digital media, we selected authors who assisted us in the delimitation of our research object, as well as in the understanding of the historical, social, cultural and political context in which the author/work is inserted. In this analysis, we start from the premise that art and theater themselves play an important role in the global development of individuals. From this perspective, we conceive, according to Konder (2013), that artistic activities preserve inside them important issues associated with men's creativity in the production process of existence. Based on this assumption, we try to answer two main questions: What are the aesthetic approaches to the dialogue in the TO and the respective criticisms that Boal presented to them? How does theoretical-methodological unity of TO contribute to human formation? In order to detail these questions, as well as regarding their objectives, we disserted on the first chapter, about the creation of Poetic Theater of the Oppressed in connection with its historical context. From this angle, we reflect on the political, social and cultural conjuncture that marked the advance of conservative forces and, at the same time, promoted a movement of contestation and proposition of alternative social projects, particularly in the context of the culture in the Brazil during the military dictatorship (1964-1985) and also in the world, in the central decades of the twentieth century. The second chapter contemplates the origin of the theater and its pedagogical heritage linked to the production of the existence. In it we inquire the conception of art and theater, especially the aesthetic discussion present in the poetics of Aristotle, Machiavelli, Hegel and Brecht, on which Boal (2013) articulated his critiques and contributions. In the last chapter, analyzing the theatrical reports of the experiences from the Boal Forum-Theater (2008), experienced in Europe in the 1970s, we point out the relations between the TO and the theatrical theories discussed in the previous chapters, as well as we evidence the theoretical-theoretical unity. Boal's proposal as we evidence the theatrologist's concern with the individual and social transformation of the spectators into spect-actors. Through this study, we conclude that the pedagogical dimension of TO results from its theoretical-methodological unity expressed in the understanding that dramatic art through communication and dialogue teaches men the ways that body and mind must go through to become protagonists of their own history, by the mediation of human formation